Cyber aggression-victimization among Malaysians youth / Sarina Yusuf ... [et al.] - Yusuf, Sarina; Mohamed Al-Majdhoub, Fatima; Mubin, Nur Nadia; Chaniago, Rizky Hafiz; Rahim Khan, Fazal (Universiti Teknologi MARA, 2021)
Cyber aggression has become a growing problem in today's society. It offers convenient opportunities to humiliate, bully, or harass others online. Global studies on cyber aggression found that youths who were aggressed online reported feeling depressed, anxious and afraid. They showed poor academic performance, and experienced eating disorders, alcohol, drugs and substance abuse. Therefore the study aimed to investigate the interrelationships between predictive factors namely peer attachment, parental attachment, exposure to the Internet and cyber aggression-victimization among youths. The renowned general aggression model (GAM) was applied to understand the phenomenon. A sample of 430 urban youths aged between 13 and 18 years living within Klang Valley area were randomly selected to participate in the study. Data were gathered through self-report questionnaires and later analyzed using SPSS and AMOS. The results revealed several noteworthy findings; most of respondents made use of the Internet for approximately 7 to 21 hours per day during weekends mainly for surfing social media, followed by entertainment and online games. A relatively significant number of youths were engaged with cyber victimization through written-verbal and online exclusion. Finally, the structural path analysis indicates that Internet exposure is the strongest predictor associated with cyber aggression-victimization. Based on these findings, the implications and recommendations for future investigations with reference to the current theoretical framework and empirical findings on cyber aggression-victimization are thoroughly discussed.